Pollution assessment and mercury leaching using environmentally friendly solvents from small-scale gold mine wastes in Camarines Norte - Aglibot, Jan Melchor B.; Tanciongco, Alexandria M.; Quierrez, Rico Neil M.; Gervasio, John Henry C.; Rasay, Anie Felicia P.; Acampado, Jesica B.; Peregrino, Fern Rose A.; Estoque, Jessa Mae V.; Samaniego, Jessie O. (Brawijaya University, 2025)
Potentially toxic elements (PTEs) have become a significant global concern due to their detrimental effects on both ecological and public health. Monitoring these elements is crucial in areas suspected of having high concentrations. In Camarines Norte, small-scale gold mining (SSGM) activities have been linked to elevated mercury levels in soils and sediments, as it is commonly used in the gold extraction process. In this study, six (6) SSGM wastes from Camarines Norte were collected, analyzed, characterized, and assessed for pollution by eight (8) PTEs: arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), nickel (Ni), lead (Pb), zinc (Zn), and mercury (Hg). Analytical techniques such as energy dispersive x-ray fluorescence (EDXRF), x-ray diffraction (XRD), inductively coupled plasma – mass spectrometry (ICP-MS), and direct mercury analyzer (DMA) were utilized. Analysis shows quartz (SiO?) as the primary mineral among all samples, with some also containing albite, biotite, kaolinite, microcline, and sphalerite. Pollution was assessed using enrichment factor (EF) and index of geoaccumulation (Igeo), which showed that the SSGM waste samples were extremely enriched and contaminated with As, Cd, Cu, Hg, Pb, and Zn. Gold concentrations were also measured, revealing high levels of enrichment in the samples. Furthermore, one of the SSGM waste samples underwent Hg leaching using environmentally friendly solvents, including deep eutectic solvents (DES). The reduced mercury concentrations after leaching demonstrate the potential application of DES for mercury remediation.